Pedagogy of Karakalpak People is the Main Factor of Patriotic Education Development in Youth - Orazimbetov Yermekbay Keulimjaevich (Web of Journals Publishing, 2023)
This article describes the ideas of patriotism, their importance in educating the young generation, the views of great thinkers about patriotism, and the traditions of patriotism in Karakalpak folk pedagogy.
Keywords: Karakalpak folk pedagogy, patriotism, homeland, history, views of great thinkers on patriotism.